Trade and Peace within the Gift Theory from a Behavioral Economics Perspective - Banu Özüşen; Levent Kösekahyaoğlu (İstanbul Üniversitesi Sosyoloji Dergisi)
Trade has been a fundamental aspect of human societies throughout history, shaping economic, social, and cultural relationships. Economic studies rooted in the “trade promotes peace” premise have shown that trade can both foster and maintain peace. This study substantiates this hypothesis by drawing upon archeological and anthropological evidence. Archeology provides important insights into trade objects, while anthropology is a source of understanding human behavior in exchange-based relationships. Meanwhile, economics analyzes the choices and behaviors of individuals, exploring the mechanisms underpinning human survival strategies and decision-making processes. This study bridges the realms of economics and anthropology by examining the economic, cultural, and legal phenomena of pre-monetary societies from the perspective of Marcel Mauss’s seminal work, “The Gift.” Specifically, it investigates how the trade built on the foundation of gift-giving can contribute to peaceful relations. The framework for this analysis encompasses utilitarianism, legal bonds, commercial relationships, and peace. Moreover, it offers a comparative perspective between historical and contemporary societies. Gift theory is deeply rooted in utilitarianism, aligning with the moral philosophy that individuals should seek happiness in their pursuits. Importantly, this study is not limited to a specific historical period. Recent research, supported by archeological and anthropological sources, highlights the existence of peaceful relations based on barter, gift exchange, or trade systems. Through this study, we aspire to make a valuable contribution to ongoing research on trade and peace, as well as interdisciplinary investigations rooted in the basis of gift theory.